METHODS OF DETERMINATION OF EFFICIENCY OF THE CENTRIFUGAL SUPERCHARGER TAKING INTO ACCOUNT ENERGY LOSSES - Oleynik, Yuriy Anatolyevich; Saprykin, Sergey Alekseevich; Naumenko, Svetlana (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2019)
Three methods of determination of the efficiency of the centrifugal supercharger (CS) where except thermal losses and losses on friction in bearings and consolidations of CS losses of energy for the following processes are considered are received: friction of the CS driving wheel in the gas environment, overflowing of gas through consolidations of CS, gas flow in inter step cavities of CS. Methods consider three various approaches to calculation of the losses of energy connected with gas flow in inter step cavities of CS. The first method considers gasdynamic losses depending on an expense and density of gas. The second method considers gasdynamic losses depending on full specific work in CS steps. The third method considers gasdynamic losses depending on specific work of Euler in CS steps. Calculation of pressure losses is carried out to CS steps for 5-7 step CS taking into account practical data on the CS parameters. Practical values for CS efficiency by one of the received methods are calculated. In calculations comparisons of efficiency of CS taking into account all losses of energy and without gasdynamic losses of energy are carried out.